2005
DOI: 10.1100/tsw.2005.51
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Microbiological Aspects of Epileptic Seizures in the Tropical Countries with Specific Focus on Nigeria

Abstract: Epilepsy is a common neurological disorder; however, in Nigeria and other tropical regions, the causes of epileptic seizures differ greatly in etiology. This paper is an attempt to highlight some possible microbiological aspects of epileptic seizures. A literature review was carried out to identify the extent to which microbial infections were involved in the elicitation of epileptic seizures. Data were collected from several clinics in the community and hospitals in Nigeria and correlated with the evidence fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Other studies in Africa have also demonstrated that the cause of epilepsy can frequently be unknown [41][42][22]. Inability to determine the cause of epilepsy is largely due to financial and diagnostic limitations at the point of care [18]. Further, genetic and metabolic testing is not available locally and performance of these tests by overseas healthcare partners is associated with significant financial costs and time delays as has been our experience.…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…Other studies in Africa have also demonstrated that the cause of epilepsy can frequently be unknown [41][42][22]. Inability to determine the cause of epilepsy is largely due to financial and diagnostic limitations at the point of care [18]. Further, genetic and metabolic testing is not available locally and performance of these tests by overseas healthcare partners is associated with significant financial costs and time delays as has been our experience.…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…More than 20% of childhood epilepsy is associated with genetic inheritance [ 19 ]. Furthermore, parasitic infections like onchocerca volvulus, neurocysticercosis, and infection with plasmodium species are associated with increased rate of childhood epilepsy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%